Opioids and Viral Infections: A Double-Edged Sword - Tahamtan, Alireza; Tavakoli-Yaraki, Masoumeh; Mokhtari-Azad, Talat; Teymoori-Rad, Majid; Bont, Louis; Shokri, Fazel; Salimi, Vahid (Frontiers in Microbiology, 2016)
Opioids and their receptors have received remarkable attention because they have the ability to alter immune function, which affects disease progression. In vitro and in vivo findings as well as observations in humans indicate that opioids and their receptors positively or negatively affect viral replication and virus-mediated pathology. The present study reviews recent insights in the role of opioids and their receptors in viral infections and discusses possible therapeutic opportunities. This review supports the emerging concept that opioids and their receptors have both favorable and unfavorable effects on viral disease, depending on the type of virus. Targeting of the opioid system is a potential option for developing effective therapies; however caution is required in relation to the beneficial functions of opioid systems.